COOPERATIVE LEARNING MODEL TYPE STAD: HOW DOES IT’S IMPACT ON STUDENTS KNOWLEDGE ABOUT HEAT AND TEMPERATURE - Olyivia Retdwina Rusma; Rani Oktavia (Universe, 2023)
One of the subjects that plays an important role in the development of the times is science. Science subjects aim to equip students with knowledge related to everyday life and train them to think scientifically. Therefore the call for learning objectives in science is something that needs to be prioritized by the teacher. One of the steps that can be taken by the teacher is to apply a learning model that is in accordance with the characteristics of the material in science subjects. One model that can be applied by teachers is the STD type of cooperative learning model. The purpose of this study was to see the effect of the STAD type cooperative learning model on students' cognitive learning outcomes on temperature, heat and expansion of SMPN 28 Padang.This research is a type of quasi-experimental research with nonequivalent control group research design. The sample in this study used a purposive sampling technique. Statistical analysis in this study used SPSS version 25. Based on the hypothesis test, a significance value of 0.735 was obtained, which means that there was no effect of the STAD type cooperative learning model on students' cognitive learning outcomes on temperature, heat, and expansion for class VII SMPN 28 Padang. There are several inhibiting factors on students' cognitive learning outcomes including student character, student interest in learning, various student backgrounds, students' basic mathematical abilities and model adjustments that have just been implemented at SMPN 28 Padang.